Metal lithium negative electrode, secondary battery, battery module, battery pack and power-consuming device
By using a composite structure of copper mesh and fiber layer on the negative electrode of the battery, the growth of lithium dendrites is suppressed, and the safety hazards of metal lithium negative electrodes are solved, and the cycle life and safety of the battery are improved.
Patent Information
- Application Number
- CN202111367364.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-11-18
AI Technical Summary
Existing metal lithium as the negative electrode of the battery has safety risks, which is prone to lithium dendrites, resulting in irreversible capacity loss and short circuit risk.
The copper mesh is used as the substrate, plated with metal lithium, and is composited with the fiber layer. Through the pore structure of the copper mesh and the support of the fiber layer, the overgrowth of lithium dendrites is inhibited.
Effectively inhibit the overgrowth of lithium dendrites, avoid puncture of the separator and irreversible loss of capacity, and improve the cycle life and safety of the battery.
Smart Images

Figure CN115832323B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a metal lithium negative electrode, a secondary battery, a battery module, a battery pack, and an electrical device. Background Art
[0002] Metallic lithium has an extremely high theoretical capacity and a very low redox potential. It is an ideal negative electrode material for lithium-ion batteries. Lithium batteries with metallic lithium as negative electrodes have great application prospects in the development of future chemical power sources. However, metallic lithium as the negative electrode of the battery has safety hazards. During the charging and discharging process, as lithium metal is continuously deposited and dissolved, lithium dendrites are easily generated. Excessively grown lithium dendrites will not only become "dead lithium", causing irreversible loss of capacity, but will also pierce the diaphragm, causing the battery to short-circuit, posing a risk of fire. Summary of the invention
[0003] The present application provides a metallic lithium negative electrode, a secondary battery, a battery module, a battery pack and an electrical device to solve the problem that the existing metallic lithium as the negative electrode of the battery is prone to produce lithium dendrites. The excessive growth of lithium dendrites will not only become "dead lithium" and cause irreversible loss of capacity, but will also pierce the diaphragm, causing the battery to short-circuit and posing a risk of fire.
[0004] The present application provides a metallic lithium negative electrode, which comprises a substrate, metallic lithium and a fiber layer, wherein the substrate comprises a copper mesh, the copper mesh is plated with metallic lithium, and the copper mesh is composited with the fiber layer.
[0005] By using the copper mesh as the base support structure, the metal lithium is supported. During the battery charge and discharge cycle, the metal lithium tends to deposit between the pores of the copper mesh, which can inhibit the excessive growth of lithium dendrites and avoid the risk of piercing the diaphragm and causing irreversible capacity loss. By designing a fiber layer on the metal lithium negative electrode, after the copper mesh is plated with metal lithium, the fiber layer is composited with the copper mesh. The fiber layer can serve as a support structure for the copper mesh, which can further improve the support stability of the copper mesh and also protect the metal lithium.
[0006] In one possible design, the copper mesh has a pore area of 1×10 -4 mm 2 -4×10 -4 mm 2 .
[0007] By rationally selecting the pore area of the copper mesh, the energy density of the negative electrode can be guaranteed while providing deposition space for lithium metal. -4 mm 2 When the pore area of the copper mesh is larger than 4×10 -4mm 2 When the negative electrode structure is not strong enough, it is prone to collapse, deformation and other problems.
[0008] In one possible design, the diameter of a single copper wire in the copper mesh is 1 mm to 2 mm.
[0009] By rationally selecting the diameter of a single copper wire in the copper mesh, the strength of the copper mesh can be effectively guaranteed, thereby providing a stable support for metallic lithium.
[0010] In a possible design, the substrate further includes copper foil connected to both sides of the copper mesh.
[0011] By setting copper foil on both sides of the copper mesh, it can be used as a current collector and cut into negative electrode tabs for preparing a lithium negative electrode sheet with a wound structure.
[0012] In one possible design, the fiber layer has a thickness of 1 mm to 2 mm.
[0013] By rationally selecting the thickness of the fiber layer, better protection of metallic lithium can be achieved.
[0014] The present application provides a method for preparing a metallic lithium negative electrode, comprising the following steps:
[0015] preparing a copper mesh;
[0016] The copper mesh is subjected to surface treatment to remove the surface oxide layer, and then metallic lithium is plated on the copper mesh;
[0017] The copper mesh plated with metallic lithium is compounded with the fiber layer to prepare a metallic lithium negative electrode.
[0018] By using a copper mesh as a substrate, plating metallic lithium on its surface, and then compounding the fiber layer with the copper mesh, during the cycle, lithium tends to deposit between the pores of the copper mesh, which can inhibit the excessive growth of lithium dendrites and avoid risks such as piercing the diaphragm.
[0019] In one possible design, the rate of plating metallic lithium on the copper grid is 20μA-40μA for 4h-8h.
[0020] By reasonably selecting the speed of plating metallic lithium on the copper mesh, the uniformity of lithium plating can be ensured and the shedding of lithium metal caused by uneven lithium plating can be avoided.
[0021] In a possible design, the fiber layer is a glass fiber layer, a polypropylene fiber layer, a polyacrylonitrile fiber layer or a polyester fiber layer.
[0022] In one possible design, the lamination method is roll pressing or chemical cross-linking.
[0023] The fiber layer is compounded with the copper mesh by rolling or chemical cross-linking to support the copper mesh and protect the metallic lithium.
[0024] In one possible design, the chemical cross-linking method includes the following steps:
[0025] The initiator and the polymer monomer are dispersed in an organic solvent to form a mixed solution; the mixed solution is coated on a copper mesh plated with metallic lithium, and a polymerization reaction occurs under the action of the initiator to form a fiber layer on the copper mesh.
[0026] By utilizing the space between the grids of the copper mesh to accurately position the polymer monomers on the surface of the metallic lithium, the polymer monomers can form a dense protective layer on the surface of the metallic lithium at the molecular level through the initiator. Compared with the fiber layer directly coated on the surface of the metallic lithium, the evaporation of the solution during the drying process will cause gaps with the metallic lithium or other substrates. The chemical cross-linking method used in this application is particularly effective in protecting the metallic lithium negative electrode.
[0027] In a possible design, the polymer monomer is one of methyl methacrylate, styrene, acrylonitrile, and 1,3-dioxolane; the initiator is lithium bis(fluorosulfonyl)imide; the polymerization reaction is carried out under the protection of an inert gas atmosphere; the polymerization reaction temperature is 50°C-60°C; and the polymerization reaction time is 20min-40min.
[0028] The present application also provides a secondary battery, comprising the above-mentioned metal lithium negative electrode or the metal lithium negative electrode prepared by the above-mentioned preparation method.
[0029] The present application also provides a battery module, comprising the above-mentioned secondary battery.
[0030] The present application also provides a battery pack, comprising the above-mentioned battery module.
[0031] The present application also provides an electrical device, comprising at least one selected from the above-mentioned secondary battery, the above-mentioned battery module or the above-mentioned battery pack.
[0032] Beneficial effects of this application:
[0033] The present application discloses a metal lithium negative electrode including a substrate, metal lithium and a fiber layer, wherein the substrate includes a copper mesh, the copper mesh is plated with metal lithium, and the copper mesh is composited with the fiber layer. By using the copper mesh as the substrate support structure, the metal lithium is supported. During the battery charge and discharge cycle, the metal lithium tends to be deposited between the pores of the copper mesh, which can inhibit the excessive growth of lithium dendrites and avoid the occurrence of safety risks such as irreversible capacity loss and puncture of the diaphragm. By designing a fiber layer on the metal lithium negative electrode, after the copper mesh is plated with metal lithium, the fiber layer is composited with the copper mesh, and the fiber layer can be used as a support structure for the copper mesh, which can further improve the support stability of the copper mesh, and can also protect the surface of the metal lithium from air.
[0034] It should be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic structural diagram of the metal lithium negative electrode provided in the present application in the first embodiment;
[0036] Figure 2 This is a schematic diagram of the structure of the substrate in the metal lithium negative electrode in the embodiment of the present application;
[0037] Figure 3 This is a schematic diagram of the structure after metal lithium is plated on the substrate in the metal lithium negative electrode in the embodiment of the present application;
[0038] Figure 4 A schematic diagram of the structure of the metal lithium negative electrode provided in the present application in the second embodiment;
[0039] Figure 5 This is a diagram showing the structural changes during the preparation of the metal lithium negative electrode of this application;
[0040] Figure 6 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0041] Figure 7 yes Figure 6 An exploded view of a secondary battery according to an embodiment of the present application is shown;
[0042] Figure 8 is a schematic diagram of a battery module according to an embodiment of the present application;
[0043] Fig. 9 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0044] Fig.10 yes Figure 8 An exploded view of a battery pack according to an embodiment of the present application is shown;
[0045] Fig.11is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source;
[0046] Fig.12 This is a comparison chart of the cycle performance tests of button batteries prepared with different metal lithium negative electrodes.
[0047] Reference numerals:
[0048] 1- substrate;
[0049] 11- copper mesh;
[0050] 12- copper foil;
[0051] 2-metal lithium;
[0052] 3-Fiber layer;
[0053] 4-Battery pack;
[0054] 5-Upper box;
[0055] 6-Lower box;
[0056] 7-Battery module;
[0057] 8- Secondary battery;
[0058] 81-housing;
[0059] 82-electrode assembly;
[0060] 83-Top cover assembly.
[0061] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application. DETAILED DESCRIPTION
[0062] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0063] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0064] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0065] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0066] It should be noted that the directional words such as "upper", "lower", "left", and "right" described in the embodiments of the present application are described at the angles shown in the accompanying drawings and should not be understood as limiting the embodiments of the present application. In addition, in the context, it is also necessary to understand that when it is mentioned that an element is connected to another element "upper" or "lower", it can not only be directly connected to another element "upper" or "lower", but also indirectly connected to another element "upper" or "lower" through an intermediate element.
[0067] With the increasing popularity of portable electronic products such as laptops and mobile phones, as well as the development of electric vehicles and energy storage batteries, people have put forward higher requirements on the energy density, service life and cost of power sources. Lithium-ion batteries with small size, light weight, environmental friendliness and high specific energy have been widely used and are gradually replacing more traditional batteries such as zinc-manganese batteries, lead-acid batteries, cadmium-nickel batteries and metal hydride batteries. As a new generation of high-energy power sources, lithium-ion batteries have developed in response to the needs of economic development, resource utilization and environmental protection, but at the same time, higher requirements have been placed on the structure and performance of lithium-ion batteries, and the positive and negative electrode materials in lithium-ion batteries are facing new challenges.
[0068] At present, industrialized lithium-ion batteries with graphite as negative electrodes can hardly meet the increasing demand for specific energy. The theoretical specific capacity of metallic lithium is 3860mAh / g, and the redox potential is -3.04V (to standard hydrogen electrode). It is an ideal negative electrode material for lithium-ion batteries and has great application prospects. However, metallic lithium as a negative electrode material for batteries has safety hazards. During the discharge process, metallic lithium will dissolve into lithium ions, and during the charging process, lithium ions will be reduced to metallic lithium. With the continuous deposition and dissolution of lithium metal, due to thermodynamic reasons, lithium will be deposited unevenly during the reduction process, resulting in the generation of lithium dendrites. Excessive growth of lithium dendrites will not only damage the solid electrolyte interface film, but also cause the exposed lithium to continuously react with the electrolyte, consume the electrolyte, and pierce the diaphragm, causing a short circuit inside the battery, causing a fire or even an explosion. In addition, lithium dendrites are easy to fall off from the electrode, so they cannot be effectively utilized, forming "dead lithium", resulting in battery capacity loss.
[0069] In view of the fact that the existing negative electrode of the battery is prone to produce lithium dendrites, the excessive growth of lithium dendrites will destroy the solid electrolyte interface membrane, and may also pierce the diaphragm, causing the battery to short-circuit, and may also become "dead lithium", causing irreversible loss of capacity. The applicant has discovered that metallic lithium can be plated on a substrate with a mesh structure to form a metallic lithium negative electrode, so that during the charge and discharge cycle of the battery, lithium tends to deposit between the mesh pores, which can inhibit the excessive growth of lithium dendrites, thereby avoiding the occurrence of problems such as piercing the diaphragm and causing irreversible loss of capacity due to excessive growth of lithium dendrites.
[0070] Based on the above considerations, in order to solve the problems that the excessive growth of existing lithium dendrites may destroy the solid electrolyte interface membrane, pierce the diaphragm, cause the battery short circuit, and become "dead lithium", causing irreversible loss of capacity, the inventors have designed a metal lithium negative electrode after in-depth research. The metal lithium negative electrode includes a substrate, metal lithium and a fiber layer, the substrate includes a copper mesh, the copper mesh is plated with the metal lithium, and the copper mesh is composited with the fiber layer.
[0071] Such a metal lithium negative electrode is based on a copper mesh, and after metal lithium is plated on the surface, the copper mesh supports the metal lithium. The lithium battery using this metal lithium negative electrode can effectively improve the cycle life of the battery. At the same time, during the cycle, the metal lithium tends to deposit between the pores of the copper mesh, which can inhibit the excessive growth of lithium dendrites and avoid the risk of piercing the diaphragm and causing irreversible capacity loss. A fiber layer is designed on the metal lithium negative electrode. After metal lithium is plated on the copper mesh, the fiber layer is composited with the copper mesh. The fiber layer can serve as a supporting structure for the copper mesh, further improving the support stability of the copper mesh, and can also protect the metal lithium surface from air.
[0072] The metal lithium negative electrode disclosed in the embodiment of the present application can be used to prepare a battery cell, specifically, a battery cell that is not limited to a wound battery cell. The metal lithium negative electrode disclosed in the embodiment of the present application can also be used in, but not limited to, energy storage devices such as lithium-ion batteries. During the battery cycle charge and discharge process, the excessive growth of lithium dendrites can be suppressed, thereby avoiding the occurrence of problems such as piercing the diaphragm and causing irreversible loss of capacity due to the excessive growth of lithium dendrites.
[0073] According to some embodiments of the present application, Figure 1 , Figure 2 and Figure 3 As shown, Figure 1 is a schematic diagram of the structure of a metal lithium negative electrode according to some embodiments of the present application, Figure 2 is a schematic structural diagram of a substrate in a metal lithium negative electrode according to some embodiments of the present application, Figure 3The schematic diagram of the structure of the metal lithium negative electrode after metal lithium is plated on the substrate in some embodiments of the present application. The present application provides a metal lithium negative electrode, which includes a substrate 1, metal lithium 2 and a fiber layer 3, wherein the substrate 1 includes a copper mesh 11, the copper mesh 11 is plated with metal lithium 2, and the copper mesh 11 is composited with the fiber layer 3.
[0074] Metallic lithium 2 is the metal element with the strongest metallic activity and the smallest density among the known elements. Lithium has a large charge density and a stable helium-type double electron layer. Lithium easily polarizes other molecules or ions, but it itself is not easily polarized. The theoretical specific capacity of metallic lithium 2 is 3860mAh / g, and the redox potential is -3.04V (to standard hydrogen electrode).
[0075] The substrate 1 supports the metal lithium 2. The substrate 1 includes a copper mesh 11. The metal lithium 2 is plated on the copper mesh 11. The copper mesh 11 has a porous structure. During the battery charge and discharge cycle, the metal lithium 2 tends to be deposited between the pores of the copper mesh 11, which can inhibit the excessive growth of lithium dendrites and avoid the risks of piercing the diaphragm and causing irreversible capacity loss. In some specific embodiments, before plating the metal lithium 2 on the copper mesh 11, a weak acid such as 1%-2% dilute hydrochloric acid is used for immersion and cleaning for 10min to 15min to remove the surface oxide layer.
[0076] The fiber layer 3 is a layer structure with pores, which does not react with the metal lithium 2 or the electrolyte. The fiber layer 3 is compounded with the copper mesh 11. The fiber layer 3 can serve as a support structure for the copper mesh 11, further improving the support stability of the copper mesh, and can also protect the metal lithium 2. In some specific embodiments, the fiber layer 3 can be a glass fiber layer, a polypropylene fiber layer, a polyacrylonitrile fiber layer, or a polyester fiber layer, but is not limited to these types.
[0077] By using the copper mesh 11 as the base support structure, the metal lithium 2 is supported. During the battery charge and discharge cycle, the metal lithium 2 tends to be deposited between the pores of the copper mesh 11, which can inhibit the excessive growth of lithium dendrites and avoid the risk of piercing the diaphragm and causing irreversible loss of capacity. By designing a fiber layer 3 on the metal lithium negative electrode, after the metal lithium 2 is plated on the copper mesh 11, the fiber layer 3 is composited with the copper mesh 11, and the fiber layer 3 can serve as a support structure for the copper mesh 11, which can further improve the support stability of the copper mesh 11 and can also protect the metal lithium 2.
[0078] According to some specific embodiments of the present application, the pore area of the copper mesh 11 is 1×10 -4 mm 2 -4×10 -4 mm 2 .
[0079] The pore area of the copper mesh 11 refers to the area of a single hole on the copper mesh 11. The pore area can be selected from 1×10 -4 mm 2 , 2×10 -4 mm 2 , 3×10 -4 mm 2 or 4×10 -4 mm 2 Of course, it can also be other values within the above range and is not limited here.
[0080] By properly selecting the pore area of the copper mesh 11, the energy density of the negative electrode can be guaranteed and a deposition space for the metal lithium 2 can be provided. -4 mm 2 When the pore area of the copper mesh 11 is greater than 4×10 -4 mm 2 When the negative electrode structure is not strong enough, it is prone to collapse, deformation and other problems.
[0081] According to some specific embodiments of the present application, the diameter of a single copper wire in the copper mesh 11 is 1 mm-2 mm.
[0082] The diameter of a single copper wire in the copper mesh 11 can be selected from 1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm or 2 mm, etc., and of course can also be other values within the above range, which is not limited here.
[0083] By reasonably selecting the diameter of a single copper wire in the copper mesh 11 , the strength of the copper mesh 11 can be effectively guaranteed, thereby providing a stable support for the metal lithium 2 .
[0084] According to some specific embodiments of the present application, Figure 2 and Figure 4 As shown, the substrate 1 further includes a copper foil 12 , and the copper foil 12 is connected to both sides of the copper mesh 11 .
[0085] The copper foil 12 is made of copper and other metals in a certain proportion, and is a cathodic electrolytic material with electrical conductivity. Figure 4 As shown, the copper foil 12 can be used as a current collector and can be cut into negative electrode tabs.
[0086] By arranging copper foil 12 on both sides of the copper mesh 11, it can be used as a current collector and cut into negative electrode tabs for preparing a lithium negative electrode sheet with a wound structure.
[0087] According to some specific embodiments of the present application, the thickness of the fiber layer 3 is 1 mm-2 mm.
[0088] The thickness of the fiber layer 3 can be selected from 1 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm or 2 mm, etc., and of course can also be other values within the above range, which is not limited here.
[0089] By rationally selecting the thickness of the fiber layer 3 , a better effect of protecting the metal lithium 2 can be achieved.
[0090] According to some specific embodiments of the present application, the present application also provides a method for preparing a metallic lithium negative electrode, comprising the following steps:
[0091] A copper mesh 11 was prepared.
[0092] The copper mesh 11 is surface treated to remove the surface oxide layer, and then metal lithium 2 is plated on the copper mesh 11.
[0093] The copper mesh 11 plated with the metal lithium 2 is compounded with the fiber layer 3 to prepare a metal lithium negative electrode.
[0094] The size of the copper mesh 11 can be designed according to the actual application scenario. The surface of the copper material is relatively easy to oxidize to form an oxide layer. The presence of the oxide layer affects the conductive properties of the copper mesh 11 and the plating effect of the metal lithium 2 on the copper mesh 11. Therefore, before plating the metal lithium 2 on the copper mesh 11, the copper mesh 11 needs to be surface treated to remove the surface oxide layer. The surface treatment method can be a physical method or a chemical method. In some specific embodiments, the surface treatment method is a chemical method. Specifically, the chemical method can be to soak and clean the copper mesh 11 in a weak acid such as 1% to 2% dilute hydrochloric acid for 10 to 15 minutes.
[0095] By using the copper mesh 11 as a substrate, plating metallic lithium 2 on its surface, and then compounding the fiber layer 3 with the copper mesh 11, during the cycle process, lithium tends to deposit between the pores of the copper mesh 11, which can inhibit the excessive growth of lithium dendrites and avoid the risk of piercing the diaphragm.
[0096] According to some specific embodiments of the present application, the speed of plating the metal lithium 2 on the copper mesh 11 is 20 μA-40 μA, and the time is 4h-8h.
[0097] The speed of plating metal lithium 2 on the copper mesh 11 can be selected from 20μA, 25μA, 30μA, 35μA or 40μA, etc., and the time can be selected from 4h, 5h, 6h, 7h or 8h, etc., of course, it can also be other values within the above range, which is not limited here.
[0098] By rationally selecting the speed of plating the metallic lithium 2 on the copper mesh 11 , the uniformity of lithium plating can be ensured, and the shedding of lithium metal due to uneven lithium plating can be avoided.
[0099] According to some specific embodiments of the present application, the compounding method is rolling or chemical cross-linking.
[0100] Rolling refers to a process of forming various complex parts by the principle of rolling extrusion based on the plastic movement characteristics of the material. The rolling in the present application specifically refers to compounding the ready-made fiber layer 3 with the copper mesh 11 by rolling extrusion.
[0101] Chemical crosslinking refers to the process in which macromolecular chains are linked together by chemical bonds under the action of light, heat, high-energy radiation, mechanical force, ultrasound and crosslinking agents to form a network or body structure polymer. The chemical crosslinking of the present application specifically refers to the process in which the polymer monomers used to prepare the fiber layer 3 undergo a polymerization reaction under the action of an initiator at a certain temperature to form the fiber layer 3 on the composite copper mesh 11.
[0102] The fiber layer 3 and the copper mesh 11 are compounded together by rolling or chemical cross-linking, so as to support the copper mesh 11 and protect the metal lithium 2 .
[0103] According to some specific embodiments of the present application, the chemical cross-linking method comprises the following steps:
[0104] The initiator and the polymer monomer are dispersed in an organic solvent to form a mixed solution; the mixed solution is coated on the copper mesh 11 plated with the metallic lithium 2, and a polymerization reaction occurs under the action of the initiator to form the fiber layer 3 on the surface of the metallic lithium.
[0105] The polymer monomer may be selected from acrylates, cycloalkanes, olefins and olefin nitriles. In some specific embodiments, the polymer monomer is one of methyl methacrylate, styrene, acrylonitrile and 1,3-dioxolane.
[0106] The organic solvent can be selected from alkanes, olefins, alcohols, aldehydes, amines, esters, ethers, ketones, aromatic hydrocarbons, hydrogenated hydrocarbons, terpene hydrocarbons, halogenated hydrocarbons, heterocyclic compounds, nitrogen-containing compounds and sulfur-containing compounds, etc. In some specific embodiments, the organic solvent can be 1,2-dimethoxyethane or acetone.
[0107] Initiators refer to a class of compounds that are easily decomposed into free radicals (i.e., primary free radicals) by heat, which can be used to initiate free radical polymerization and copolymerization reactions of olefins and dienes, and can also be used for cross-linking and curing of unsaturated polyesters and cross-linking reactions of polymers. The initiator can be an organic peroxide initiator, an inorganic peroxide initiator, an azo initiator, and a redox initiator. In some specific embodiments, the initiator is lithium bis(fluorosulfonyl)imide, which does not introduce new impurities into the battery system compared to other initiators.
[0108] By utilizing the space between the grids of the copper mesh 11 to accurately position the polymer monomer on the surface of the metal lithium 2, the polymer monomer can form a dense protective layer on the surface of the metal lithium at the molecular level through the initiator. Compared with the fiber layer 3 directly coated on the surface of the metal lithium 2, the evaporation of the solution during the drying process will cause gaps between the metal lithium 2 and other substrates. The chemical cross-linking method used in this application is particularly effective in protecting the negative electrode of the metal lithium 2.
[0109] According to some specific embodiments of the present application, the polymerization reaction is carried out under the protection of an inert gas atmosphere, the polymerization reaction temperature is 50° C.-60° C., and the polymerization reaction time is 20 min-40 min.
[0110] Inert gas can protect the reactants from direct contact with air and avoid the formation of by-products during the reaction. Inert gas can be helium, neon, argon, krypton, xenon or radon.
[0111] The polymerization reaction temperature may be selected from 50°C, 52°C, 54°C, 56°C, 58°C or 60°C, etc., and may also be other values within the above range, which is not limited here.
[0112] The polymerization reaction time can be selected from 20 min, 25 min, 30 min, 35 min or 40 min, etc., and of course it can also be other values within the above range, which is not limited here.
[0113] By controlling the polymerization reaction time, polymerization reaction temperature and polymerization reaction atmosphere during the chemical cross-linking process, the chemical cross-linking is made more complete, so that the fiber layer 3 is more stably and evenly compounded on the copper mesh 11 .
[0114] According to some specific embodiments of the present application, the present application also provides a battery cell, which includes the metal lithium negative electrode disclosed in the present application.
[0115] The battery cell can be a wound battery cell or a laminated battery cell. In some specific embodiments, the battery cell is a wound battery cell, and the preparation method of the wound battery cell includes the following steps: (1) adding copper fluoride to a lithium nitrate solution to form a mixed solution, and immersing the metal lithium negative electrode of the present application in the mixed solution to form a surface passivation film to avoid contact between the metal lithium and the air during the manufacturing process. (2) cutting the copper foil 12 on the substrate 1 of the metal lithium negative electrode into the lugs according to the die-cutting size, and preparing a wound structure battery cell with the positive electrode and the isolation film.
[0116] According to some specific embodiments of the present application, the present application also provides a secondary battery.
[0117] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0118] [Positive electrode]
[0119] The positive electrode plate includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0120] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0121] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0122] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0123] In some embodiments, the positive electrode film layer may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0124] In some embodiments, the positive electrode film layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0125] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0126] [Negative electrode]
[0127] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0128] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0129] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0130] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0131] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0132] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0133] In some embodiments, the negative electrode film layer may also optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0134] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0135] [Electrolytes]
[0136] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0137] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0138] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0139] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0140] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0141] [Isolation film]
[0142] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0143] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0144] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process.
[0145] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0146] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0147] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 6 The secondary battery 8 is a square structure as an example.
[0148] In some embodiments, reference Figure 7 , the outer packaging may include a shell 81 and a cover plate 83. Among them, the shell 81 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 81 has an opening connected to the receiving cavity, and the cover plate 83 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 82 through a winding process or a lamination process. The electrode assembly 82 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 82. The number of electrode assemblies 82 contained in the secondary battery 8 can be one or more, and those skilled in the art can select according to specific actual needs.
[0149] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0150] Figure 8 7 is an example of a battery module. Figure 8 In the battery module 7, the plurality of secondary batteries 8 may be arranged in sequence along the length direction of the battery module 7. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 8 may be fixed by fasteners.
[0151] Optionally, the battery module 7 may further include a housing having a housing space, and the plurality of secondary batteries 8 are housed in the housing space.
[0152] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0153] Fig. 9 and Fig.10 4 is an example of a battery pack. Fig. 9 and Fig.10The battery pack 4 may include a battery box and a plurality of battery modules 7 disposed in the battery box. The battery box includes an upper box body 5 and a lower box body 6. The upper box body 5 can cover the lower box body 6 and form a closed space for accommodating the battery modules 7. The plurality of battery modules 7 can be arranged in the battery box in any manner.
[0154] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0155] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0156] Fig.11 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0157] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0158] Example
[0159] The following describes the performance evaluation of the examples and comparative examples of the metal lithium negative electrode according to the present application.
[0160] Example 1
[0161] 1. Preparation method of metal lithium negative electrode
[0162] The structural changes during the preparation process are as follows Figure 5 As shown:
[0163] S1: Prepare a copper mesh 11 of suitable width, with a pore size of 1×10 -4 mm 2 between,
[0164] The copper mesh 11 is soaked and cleaned in a weak acid such as 1% to 2% diluted hydrochloric acid for 10 to 15 minutes to remove the surface oxide layer, and then metal lithium 2 is plated on the copper mesh 11.
[0165] S2: The copper mesh 11 plated with metal lithium 2 and the fiber layer 3 are compounded together by rolling, and the thickness of the fiber layer 3 is between 1 mm and 2 mm. Rolling parameters: speed is 1 cm / s to 10 cm / s, and force is 50N-200N.
[0166] Example 2
[0167] 1. Preparation method of metal lithium negative electrode
[0168] S1: Prepare a copper mesh 11 of suitable width, with a pore area of 1×10 -4 mm 2 .
[0169] The copper mesh 11 is soaked and cleaned in a weak acid such as 1% to 2% dilute hydrochloric acid for 10 to 15 minutes to remove the surface oxide layer, and then metal lithium 2 is plated on the copper mesh 11.
[0170] S2: The copper mesh 11 plated with the metal lithium 2 is compounded with the fiber layer 3 in a chemically cross-linked manner, and the thickness of the fiber layer 3 is between 1 mm and 2 mm.
[0171] In the chemical crosslinking process, the initiator is lithium bis(fluorosulfonyl)imide, the polymer monomer is methyl methacrylate, and the organic solvent is 1,2-dimethoxyethane. In the chemical crosslinking process, the proportion of each component in the mixed solution is: initiator 0.1%-1%wt, polymer monomer 10%-30%wt, organic solvent 69%-89.9%wt. The polymerization reaction is carried out under the protection of an inert gas atmosphere. The polymerization reaction temperature is 50°C-60°C, and the polymerization reaction time is 30 minutes.
[0172] Example 3
[0173] The metal lithium negative electrode of this embodiment is the same as that of embodiment 2 except for the following technical solutions: the pore area of the copper mesh 11 is 4×10 -4 mm 2 .
[0174] Example 4
[0175] The metal lithium negative electrode of this embodiment is the same as that of embodiment 2 except for the following technical solutions: the pore area of the copper mesh 11 is 3×10 -4 mm 2 .
[0176] Comparative Example
[0177] Conventional metallic lithium negative electrode, lithium sheet with a thickness of 0.5 mm.
[0178] Full-cell button battery assembly: After NMC523, acetylene black SP, and PVDF were blended in a mass ratio of 80:10:10, nitrogen methyl pyrrolidone was added, stirred for 2 hours to form a slurry, and evenly coated on the surface of aluminum foil with a coating machine, and then placed in a 120°C oven for forced air drying for 120 minutes to prepare a button battery positive electrode. The metal lithium negative electrodes of the above Examples 1-4 and Comparative Examples 1-3 and the prepared button battery positive electrodes were assembled into button batteries by conventional lithium battery assembly methods, wherein 1 mol / L LiTFSI was selected as the electrolyte.
[0179] The prepared button cell was subjected to a battery cycle performance test, and the test results obtained are shown in Table 1. Fig.12 As shown, Table 1 lists the 50-cycle capacity retention rate of button cells prepared with metal lithium negative electrodes as negative electrode materials in Examples 1-4 and Comparative Examples. Fig.12 The cycle performance comparison diagram of the button battery prepared with the metal lithium negative electrode as the negative electrode material of Example 2 and the comparative example is shown in FIG. Among them, the detection equipment is LAND (CT2001A), the charge and discharge voltage range is 3.0-4.3V, and the test current size is 0.1C.
[0180] Table 1 Comparison of 50-cycle capacity retention rates of button cells prepared with different metal lithium anodes as anode materials
[0181]
[0182] From the results in Table 1, it can be seen that the 50-cycle capacity retention rates of the button cells prepared with the metal lithium negative electrode of Examples 1-4 as the negative electrode material are 82.0%, 81.3%, 81.5%, and 81.8%, respectively, and the 50-cycle capacity retention rate of the button cell prepared with the metal lithium negative electrode of Comparative Example 1 as the negative electrode material is 59.7%. Fig.12 It can be seen from the comparison curve that the battery prepared using the metal lithium negative electrode of the present application has excellent cycle performance.
[0183] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A metallic lithium negative electrode, characterized in that: The metal lithium negative electrode comprises a substrate (1), metal lithium (2) and a fiber layer (3); the substrate (1) comprises a copper mesh (11), the metal lithium (2) is plated on the copper mesh (11), the copper mesh (11) has a porous structure, the copper mesh (11) is composited with the fiber layer (3), and the fiber layer (3) is a layer structure with pores.
2. The metallic lithium negative electrode according to claim 1, characterized in that The pore area of the copper mesh (11) is 1×10 - 4 mm 2 -4×10 -4 mm 2 .
3. The metallic lithium negative electrode according to claim 1, characterized in that The diameter of a single copper wire in the copper mesh (11) is 1 mm to 2 mm.
4. The metallic lithium negative electrode according to claim 1, characterized in that The substrate (1) further comprises a copper foil (12), wherein the copper foil (12) is connected to both sides of the copper mesh (11).
5. The metal lithium negative electrode according to claim 1, characterized in that The fiber layer (3) has a thickness of 1 mm to 2 mm.
6. A method for preparing a metallic lithium negative electrode, characterized in that: The steps include: preparing a copper mesh (11); The copper mesh (11) is subjected to surface treatment to remove a surface oxide layer, and then metal lithium (2) is plated on the copper mesh (11), wherein the copper mesh (11) has a porous structure; The copper mesh (11) plated with the metal lithium (2) is compounded with a fiber layer (3), wherein the fiber layer (3) is a layer structure with pores, to prepare the metal lithium negative electrode.
7. The preparation method according to claim 6, characterized in that: The speed of plating the metal lithium (2) on the copper mesh (11) is 20 μA-40 μA, and the time is 4 hours-8 hours.
8. The preparation method according to claim 6, characterized in that: The fiber layer (3) is a glass fiber layer, a polypropylene fiber layer, a polyacrylonitrile fiber layer or a polyester fiber layer.
9. The preparation method according to claim 6, characterized in that: The compounding method is rolling or chemical cross-linking.
10. The preparation method according to claim 9, characterized in that: The chemical cross-linking method comprises the following steps: An initiator and a polymer monomer are dispersed in an organic solvent to form a mixed solution; the mixed solution is coated on the copper mesh (11) plated with the metal lithium (2); a polymerization reaction occurs under the action of the initiator to form the fiber layer (3) on the copper mesh (11).
11. The preparation method according to claim 10, characterized in that: The polymer monomer is one of methyl methacrylate, styrene, acrylonitrile and 1,3-dioxolane; the initiator is lithium bis(fluorosulfonyl)imide; the polymerization reaction is carried out under the protection of an inert gas atmosphere; the polymerization reaction temperature is 50° C.-60° C.; and the polymerization reaction time is 20 min-40 min.
12. A secondary battery, characterized in that: The invention comprises the metal lithium negative electrode as described in any one of claims 1 to 5 or the metal lithium negative electrode prepared by the preparation method as described in any one of claims 6 to 11.
13. A battery module, characterized in that: Includes the secondary battery as claimed in claim 12.
14. A battery pack, characterized in that: Comprising the battery module as claimed in claim 13.
15. An electrical device, characterized in that: The battery comprises at least one selected from the secondary battery of claim 12 , the battery module of claim 13 , or the battery pack of claim 14 .
Citation Information
Patent Citations
Preparation method of ultrathin lithium metal cathode
CN110504451A
Metal lithium negative electrode, and preparation method and application of metal lithium negative electrode
CN113422002A
Cited By
Metal lithium negative electrode, secondary battery, battery module, battery pack, and electric device
WO2023088078A1